Efforts to Enhance Preparedness for Forest and Land Fire Disasters - Gita Akbar, Adam; Iswara, Aditya Prana; Saputra, Hijrah (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
Forest and land fires (karhutla) represent a global issue with serious impacts on the environmennt, economy, and public health, particularly in developing countries such as indonesia. In Indonesia, forest and land fires predominantly occur in peatland areas due to climate change, land-clearing practices, adn natural factors such as the El Niño phenomenon. The research employed a Systematic Literature Review (SLR) method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, encompassing the stages of identification, screening, eligibility assessment, and analysis. The literature search and selection process resulted in 10 Indonesian-language scholarly articles published between 2014 and 2024 that were relevant to forest and land fire preparedness. The findings of the SLR indicate four primary strategies for improving preparedness: (1) education through disaster awareness programs and disaster literacy, (2) disaster simulations to enhance rapid response capabilities, (3) optimization of the role of task forces in preventive actions, and (4) technological innovations such as monitoring applications, weather modification, and business intelligence–based dashboards. Community-based approaches and policy support were also found to be effective, although challenges related to resource limitations and inter-institutional coordination remain. In conclusion, these findings emphasize that enhancing preparedness for forest and land fire disasters requires an integrated approach involving multi-stakeholder collaboration, sustained policy support, and the strengthening of community and institutional capacities.